Pottery traditions in Uzbekistan - Abdusalomov Bakhtiyor Ubaydullaevich (Genius Journals, 2022)
This article discusses the art and traditions of ceramics in Uzbekistan, what makes each region of pottery different.
Keywords: Pottery; blue glaze; decoration; pencil